2000
DOI: 10.1103/physrevlett.84.2184
|View full text |Cite
|
Sign up to set email alerts
|

Surfactant Effects and an Order-Disorder Transition in Binary Gas-Liquid Nucleation

Abstract: Density-functional theory is applied to the interaction site model to study gas-liquid nucleation in a partially immiscible binary system consisting of spherical Lennard-Jones atoms (monomers) and dumbbell molecules of two Lennard-Jones atoms (dimers). Increased interaction anisotropy between the dimer sites and monomers is shown to result in mutual enhancement of nucleation. Critical nuclei with a lamellar structure are observed at high dimer activities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 16 publications
1
8
0
Order By: Relevance
“…34 In particular, the energy parameters for the partially miscible system are ⑀ϭ⑀ 00 ϭ1.0, ⑀ 11 /⑀ 00 ϭ⑀ 22 /⑀ 00 ϭ0.6, k 01 ϭϪ0.7, k 02 ϭ0.8, and k 12 ϭ0.0 ͑hereafter this system is called the NL system͒. For the reference ''ideal'' binary mixture system, 12,29 we set the energy parameters for unlike atoms to be ⑀ 01 ϭ(⑀ 00 ϩ⑀ 11 )/2 and ⑀ 02 ϭ(⑀ 00 ϩ⑀ 22 )/2.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…34 In particular, the energy parameters for the partially miscible system are ⑀ϭ⑀ 00 ϭ1.0, ⑀ 11 /⑀ 00 ϭ⑀ 22 /⑀ 00 ϭ0.6, k 01 ϭϪ0.7, k 02 ϭ0.8, and k 12 ϭ0.0 ͑hereafter this system is called the NL system͒. For the reference ''ideal'' binary mixture system, 12,29 we set the energy parameters for unlike atoms to be ⑀ 01 ϭ(⑀ 00 ϩ⑀ 11 )/2 and ⑀ 02 ϭ(⑀ 00 ϩ⑀ 22 )/2.…”
Section: Resultsmentioning
confidence: 99%
“…In their theoretical work, however, Napari and Laaksonen found that the mutual enhancement of nucleation occurred only in monomer-rich vapors. 34 They attributed the mutual enhancement of nucleation to the reduction of the surface tension of the critical cluster. This reduction stems from the appearance of orientational surface order for the dimers at the surface of clusters.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The latter has been a focus of intensive research at the University of Helsinki where continuous observations of nucleation events (Mäkelä et al, 1997(Mäkelä et al, , 2000 and theoretical work addressing new particle formation (e.g. Laaksonen and Oxtoby, 1995;Korhonen et al, 1999;Napari and Laaksonen, 2000;Vehkamäki and Ford, 2000) have been linked with the help of multicomponent microphysical models AEROFOR2 (Pirjola and Kulmala, 2000a) and MONO32 (Pirjola and Kulmala, 2000b;Pirjola et al, 2003), applying sectional and multimodal monodisperse particle descriptions, respectively. While these models have succeeded in reproducing the qualitative features of observed phenomena, recent improvements in understanding the inital steps of particle formation and growth as well as advancements in the numerical description of particle size distribution necessitate updating of modelling tools.…”
Section: Introductionmentioning
confidence: 99%
“…The latter has been a focus of intensive research at the University of Helsinki where continuous observations of nucleation events (Mäkelä et al, 1997(Mäkelä et al, , 2000 and theoretical work addressing new particle formation (e.g. Laaksonen and Oxtoby, 1995;Korhonen et al, 1999;Napari and Laaksonen, 2000;Vehkamäki and Ford, 2000) have been linked with the help of multicomponent microphysical models AEROFOR2 (Pirjola and Kulmala, 2000a) and MONO32 (Pirjola and Kulmala, 2000b;Pirjola et al, 2003), applying sectional and multimodal monodisperse particle descriptions, respectively. While these models have succeeded in reproducing the qualitative features of observed phenomena, recent improvements in understanding the inital steps of particle formation and growth as well as advancements in the numerical description of particle size distribution necessitate updating of modelling tools.…”
Section: Introductionmentioning
confidence: 99%